Scale-up of CHO cell cultures: from 96-well-microtiter plates to stirred tank reactors across three orders of magnitude - Anne Neuss; Thomas Steimann; Jacinta Sofia Tomas Borges; Robert Dinger; Jørgen Barsett Magnus (Journal of Biological Engineering, 2025)
Abstract Background For process development in mammalian cell cultivations, scale-up approaches are essential. A lot of studies concern the scale transfer between different-sized stirred tank reactors. However, process development usually starts in even smaller cultivation vessels like microtiter plates or shake flasks. A scale-up from those small shaken devices to a stirred tank reactor is barely stated in literature for mammalian cells. Thus, this study aims to address data-driven scale-up for CHO DP12 cells. The oxygen transfer rate is used as a database. Results The cultivation conditions in microtiter plates and shake flasks are comparable when choosing the maximum oxygen transfer capacity as a scale-up parameter. The minimum cultivation volume was reduced to 400 µL in round and square 96-deep-well microtiter plates. Using a scale-up based on the maximum oxygen transfer capacity to a stirred tank reactor led to conditions with excessive hydromechanical stress. However, cultivation conditions could be reproduced in a stirred tank reactor by utilizing the volumetric power input as a scale-up parameter. Key metabolites behaved the same in all three scales and the final antibody titer was equal. Conclusion This study presents a successful replication of cultivation results for mammalian cells in microtiter plates, shake flasks and stirred tank reactors. The working volumes ranged from 0.4 to 50 and 600 mL. It offers the opportunity to adapt the method to other, more sensitive mammalian cells and to perform cost- and time-effective experiments in high-throughput.